Influence of Asthma Education on Asthma Severity, Quality of Life and Environmental Control - Johanne Côté; André Cartier; Patricia Robichaud; Hélène Boutin; Jean-Luc Malo; Michel Rouleau; Louis-Philippe Boulet (Canadian Respiratory Journal)
BACKGROUND: Several studies have examined the influence of asthma education, focusing mainly on the use of health services.